Partisipasi Masyarakat dalam Pengembangan Kampoeng Cyber sebagai Destinasi Wisata Edukasi: (Studi Di Kelurahan Gedog Kecamatan Sananwetan Kota Blitar) - Widelina Dinda Evelin; Wydha Mustika Maharani; Jalu sora Wicitra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Blitar City has various famous tourist destinations such as Bung Karno's Tomb, Kebon Rojo Park, Gebang Palace, and Ar-Rahman Mosque. However, there is one unique destination, Kampoeng Cyber, which offers a special educational tourism experience. Although the tourism sector in Blitar City is growing, the development of these destinations requires active participation from the community, not just the government. The main problem found is that community participation still varies, where most are only involved if they feel they will benefit directly. This study aims to examine how much community participation in the development of Kampoeng Cyber as an educational tourism destination, based on the theory of community participation according to Meronda (2021). This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation in Gedog Village, Sananwetan Subdistrict, Blitar City. The results showed that community participation in the development of Kampoeng Cyber is quite good, as seen from monthly meetings, local potential development programs, and regular evaluations. However, there are challenges in the form of pros and cons among the community. The main factor supporting this development is the great potential of Kampoeng Cyber in increasing community knowledge and awareness, while the obstacles are the differences in understanding and background among residents. Overall, the development of Kampoeng Cyber has had a positive impact both economically and socially, making it more widely recognized.